Towards a further understanding of prenatal thyroid theory of homosexuality: Autoimmune thyroiditis, polycystic ovary syndrome, autism and low birth weight - SABUNCUOĞLU, OSMAN TALAT (PAGEPRESS PUBL, 2017)
Research into the neurobiological origins of same-sex attraction is inconclusive. A recent theory of homosexuality posited that maternal thyroid dysfunction during pregnancy is associated with an increased rate of homosexual orientation in offspring. Relevant studies from the prenatal thyroid model perspective were reviewed, the major findings of which are as follows: i) An increased prevalence of Hashimoto's disease in lesbian women suggests a maternal and even familial presence of the same autoimmune thyroid disease. Female-to-male transsexuals and lesbian women were also reported to have higher rates of polycystic ovary syndrome (PCOS). Over the last several years, reports suggesting a strong link between PCOS and thyroid autoimmunity have accumulated. ii) The increased risk of autism spectrum disorders (ASD) in the offspring of mothers with thyroid autoimmunity in pregnancy and the association between ASD and gender dysphoria indicate a link between maternal thyroid dysfunction and gender dysphoria/same-sex attraction in the offspring. iii) The high risk of miscarriage and retarded fetal growth in pregnancies of mothers who give birth to homosexual offspring can be explained by the impact of maternal thyroid dysfunction during pregnancy. This perspective review highlights relevant research findings and integrates them into the prenatal thyroid model of homosexuality. A better understanding of the mechanisms involved in the generation of same-sex orientation will contribute to the betterment of individual lives, as well as of society.
Keywords: homosexuality; gender dysphoria; autoimmune thyroiditis; polycystic ovary syndrome; autism; birth weight; TRANSIENT CONGENITAL HYPOTHYROIDISM; TO-MALE TRANSSEXUALS; HASHIMOTOS-THYROIDITIS; SPECTRUM DISORDERS; SEXUAL ORIENTATION; HIGH PREVALENCE; GENDER IDENTITY; CHILDREN; DISEASE; FEMALE